2021
DOI: 10.1155/2021/9947811
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Internet Supply Chain Finance Based on Artificial Intelligence under the Enterprise Green Business Model

Abstract: At present, China’s economic development has made unprecedented progress, but it is also facing a severe situation, and the environmental carrying capacity has almost reached its limit. For this reason, the government vigorously promotes the construction of ecological civilization and advocates green development, circular development, and low-carbon development. Enterprise green operation is a business activity that integrates environmental protection into the whole process of enterprise operation and manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The real green practice is still limited, mainly to deal with the internal sustainable development and efficiency of enterprises. Later, with the gradual deepening of the concept of green development, the connotation of enterprise green development gradually expanded [ 13 ]. In addition to meeting the needs of the enterprise itself, it also needs to further meet the needs of the enterprise's external environment and produce positive external effects.…”
Section: Concept Definition and Theoretical Basismentioning
confidence: 99%
“…The real green practice is still limited, mainly to deal with the internal sustainable development and efficiency of enterprises. Later, with the gradual deepening of the concept of green development, the connotation of enterprise green development gradually expanded [ 13 ]. In addition to meeting the needs of the enterprise itself, it also needs to further meet the needs of the enterprise's external environment and produce positive external effects.…”
Section: Concept Definition and Theoretical Basismentioning
confidence: 99%
“…The research Jian (2022) is also included in this subject area. Zhang (2021a) concluded that the use of Internet-related technologies strongly promoted the development of supply chain finance and has far-reaching importance in solving the financing of small and medium-sized companies.…”
Section: Resultsmentioning
confidence: 99%
“…Most papers use the data-driven scientometric analysis [31,[41][42][43][44][45][46][47][48][49][50], basically aimed to investigate the progress and the possible trajectories bordering the FinTech knowledge area. Other research publications use different panel data models, owing to the lack of long time series data related to FinTech indicators and the greening policy [44].…”
Section: Discussionmentioning
confidence: 99%